Alcohol and Health Outcomes: An Umbrella Review of Meta-Analyses Base on Prospective Cohort Studies - Zhong, Lixian; Chen, Weiwei; Wang, Tonghua; Zeng, Qiuting; Lai, Leizhen; Lai, Junlong; Lin, Junqin; Tang, Shaohui (Frontiers in Public Health, 2022)
An umbrella review of meta-analyses was performed to summarize the evidence of associations between alcohol consumption and health outcomes and to assess its credibility. Meta-analyses of prospective cohort studies reporting the associations of alcohol consumption with health outcomes were identified. We recalculated the random-effects summary effect size and 95% confidence interval, heterogeneity, and small-study effect for each meta-analysis and graded the evidence. Fifty-nine publications reporting 224 meta-analyses of prospective cohort studies with 140 unique health outcomes were included, in which there were 49 beneficial associations and 25 harmful associations with nominally statistically significant summary results. But quality of evidence was rated high only for seven beneficial associations (renal cell carcinoma risk, dementia risk, colorectal cancer mortality, and all-cause mortality in patients with hypertension for low alcohol consumption; renal cell carcinoma risk, cardiovascular disease (CVD) risk in patients with hypertension and all-cause mortality in patients with hypertension for moderate consumption) and four harmful associations (cutaneous basal cell carcinoma risk for low alcohol consumption; cutaneous basal cell carcinoma risk and cutaneous squamous cell carcinoma risk for moderate alcohol consumption; hemorrhagic stroke risk for high alcohol consumption). In this umbrella review, only 11 health outcomes (5 in low alcohol consumption, 5 in moderate alcohol consumption and 1 in high alcohol consumption) with statistically significant showed high quality of epidemiologic evidence. More robust and larger prospective studies are needed to verify our results.